Genetic prediction of causal association between serum bilirubin and hematologic malignancies: a two-sample Mendelian randomized and bioinformatics study - Lu, Lihua; Luo, Luting; Li, Xiang; Liu, Wanying; Wu, Boheng; Cai, Qing; Li, Jiazheng; Huang, Yan; Chen, Yanxin; Zheng, Yongzhi; Hu, Jianda (Frontiers in Oncology, 2024)
Introduction An increasing number of cohort studies have shown a correlation between serum bilirubin and tumors, but no definitive causal relationship has been established between serum bilirubin and hematological malignancies.Therefore, the aim of the present study was to assess the causal relationship of serum bilirubin, including total bilirubin (TBIL) and direct bilirubin (DBIL), with hematological malignancies, including leukemia, lymphoma, and myeloma. Methods We used a genome-wide association study (GWAS) collection of TBIL, DBIL, and hematological malignancies data. Using two-sample Mendelian randomization(MR), we assessed the impact of TBIL and DBIL on hematological malignancies. For this study, the inverse variance weighting method (IVW) was the primary method of MR analysis. In the sensitivity analysis, the weighted median method, MR Egger regression, and MR-PRESSO test were used. To understand the mechanisms behind TBIL and DBIL, we used three different approaches based on screening single nucleotide polymorphisms (SNPs) and their associated genes, followed by bioinformatics analysis. Results The IVW test results showed evidence of effects of TBIL (odds ratio [OR]: 4.47, 95% confidence interval [CI]: 1.58-12.62) and DBIL (OR: 3.31, 95% CI: 1.08-10.18) on the risk of acute myeloid leukemia (AML).The findings from bioinformatics indicated that TBIL could potentially undergo xenobiotic metabolism through cytochrome P450 and contribute to chemical carcinogenesis. Discussion In this study, two-sample MR analysis revealed a causal relationship between TBIL, DBIL, and AML.